2019
DOI: 10.1037/spy0000141
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of exemplary parenting in competitive female youth team sport.

Abstract: This study examined how exemplary youth sport parents support their daughters in competitive team sport. Individual interviews were first conducted with eight coaches (three women and five men). Coaches were then invited to nominate exemplary youth sport parents. Interviews were subsequently conducted with 10 nominated parents (seven mothers and three fathers). Interpretive description methodology (Thorne, 2016) was used. Results were organized around three categories: being autonomy supportive (represented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Sport psychology studies have investigated the relationships between players and various components of their microsystem in-depth. This kind of knowledge could be informative for understanding what is at stake during club mutations, such as their effects on peers or teammates (e.g., Allen, 2003 ; Höll and Burnett, 2014 ; Erickson and Côté, 2016 ; Garn, 2016 ), coaches (e.g., Jowett and Poczwardowski, 2007 ; Rhind et al, 2012 ; Jowett, 2017 ), or parents and family (e.g., Horn and Horn, 2007 ; Clarke and Harwood, 2014 ; Knight et al, 2016 ; Pynn et al, 2019 ). Research to date has characterized how the components of a players environment influence their development by supporting (e.g., players stability and harmony), constraining (e.g., undermining players well-being), accelerating (e.g., increasing the performance success and satisfaction), or modifying how a player handles the impact of a problematic situation.…”
Section: Mutation As a Contextual Transitionmentioning
confidence: 99%
“…Sport psychology studies have investigated the relationships between players and various components of their microsystem in-depth. This kind of knowledge could be informative for understanding what is at stake during club mutations, such as their effects on peers or teammates (e.g., Allen, 2003 ; Höll and Burnett, 2014 ; Erickson and Côté, 2016 ; Garn, 2016 ), coaches (e.g., Jowett and Poczwardowski, 2007 ; Rhind et al, 2012 ; Jowett, 2017 ), or parents and family (e.g., Horn and Horn, 2007 ; Clarke and Harwood, 2014 ; Knight et al, 2016 ; Pynn et al, 2019 ). Research to date has characterized how the components of a players environment influence their development by supporting (e.g., players stability and harmony), constraining (e.g., undermining players well-being), accelerating (e.g., increasing the performance success and satisfaction), or modifying how a player handles the impact of a problematic situation.…”
Section: Mutation As a Contextual Transitionmentioning
confidence: 99%
“…When considering parenting styles in the sporting literature, it is generally suggested that an authoritative parenting style or an autonomy-supportive approach was most beneficial (Harwood & Knight, 2015;Pynn et al, 2019). Specifically, it appears that these approaches are associated with improved/enhanced sportspersonship, sport enjoyment, motivation, sport satisfaction, and mastery orientation (Gagné et al, 2003;Holt et al, 2009;Juntumaa et al, 2005;Pynn et al, 2019;Sapieja et al, 2011;Wright et al, 2019).…”
Section: Parents Apply An Autonomy-supportive Parenting Stylementioning
confidence: 99%
“…When considering parenting styles in the sporting literature, it is generally suggested that an authoritative parenting style or an autonomy-supportive approach was most beneficial (Harwood & Knight, 2015;Pynn et al, 2019). Specifically, it appears that these approaches are associated with improved/enhanced sportspersonship, sport enjoyment, motivation, sport satisfaction, and mastery orientation (Gagné et al, 2003;Holt et al, 2009;Juntumaa et al, 2005;Pynn et al, 2019;Sapieja et al, 2011;Wright et al, 2019). For instance, an authoritative parenting style has been associated with children displaying a higher level of mastery orientated behaviour, reduced levels of task-irrelevant and norm-breaking behaviour, and healthy perfectionism (Juntumaa et al, 2005;Sapieja et al, 2011).…”
Section: Parents Apply An Autonomy-supportive Parenting Stylementioning
confidence: 99%
See 2 more Smart Citations